Agronomic and productive characteristics of cherry tomatoes under potassium levels supplied via vinasse and mineral fertilization (Research, Society and Development, 2020)
To vinasse is a by-product of ethanol production that has a composition rich in nutrients such as potassium. The aim of this study was to evaluate the agronomic and productive characteristics of cherry tomato cultivars under application of potassium levels supplied via vinasse and mineral fertilization. The experimental design used was randomized blocks in a 5x2 factorial scheme, with 5 levels of vinasse: N1 - 100% vinasse; N2 - 80% vinasse + 20% potassium fertilization via mineral; N3 - 60% vinasse + 40% of potassium fertilization via mineral; N4 - 40% vinasse + 60% of potassium fertilization via mineral; N5 - 20% vinasse + 80% of potassium fertilization via mineral, and the other nutrients were provided by vinasse + mineral fertilization and 2 of cherry tomato cultivars (Carolina and Isla-Pró) with 4 blocks totaling 40 plots. For statistical analysis, regression and Tukey test at 1 and 5% significance were used. The Isla Pró variety had higher plant height and transverse diameter of cherry tomato fruits. The Carolina variety, on the other hand, had the highest number of flowers, clusters and fruits as well as the highest content of total soluble solids, regardless of the level of potassium supplied via vinasse. Higher levels of potassium provided by vinasse promoted a higher value in the transverse diameter of the fruits and content of total soluble solids.